Determinants of Farm Income in Integrated Rice–Beef Cattle Farming Systems in Kahu District, Bone Regency - Ahmad Zailan; Riskiyani; Hasriliandi Halim; Muh Haidir Hakim; Makmur (Tarjih : Agribusiness Development Journal, 2026)
Integrated rice–beef cattle farming systems are promoted as a sustainable agricultural strategy to improve resource-use efficiency and enhance farmers’ income through the integration of crop and livestock enterprises. However, empirical evidence regarding the determinants of farm income in integrated farming systems remains limited at the local level. This study aimed to analyze the effects of land area, production costs, and labor on farm income in integrated rice–beef cattle farming systems in Kahu District, Bone Regency. A quantitative cross-sectional survey was conducted from January to April 2025 involving 68 integrated farmers selected through simple random sampling. Data were analyzed using a log-linear multiple regression model estimated by Ordinary Least Squares (OLS). The results showed that land area had a positive and significant effect on farm income (β = 0.614; p < 0.001), while production costs (β = 0.115; p = 0.550) and labor (β = 0.048; p = 0.800) had positive but statistically insignificant effects. Simultaneously, all explanatory variables significantly affected farm income (F = 28.686; p < 0.001), with the model explaining 57.3% of the variation in farm income (R² = 0.573). These findings indicate that farm scale remains the dominant determinant of income in integrated farming systems. Policies supporting land optimization, integrated farming management, and resource-use efficiency are needed to strengthen the sustainability of smallholder farmers’ income.